PENGEMBANGAN MEDIA INTERAKTIF BERBASIS WEBSITE TERHADAP MATERI FAKTA DAN OPINI PADA SISWA KELAS V SEKOLAH DASAR - Nur Bahagia; Wiwy Triyanti Pulukadang; Fidyawati Monoarfa; Rusmin Husain; Rustam Husain; Mumammad Sarlin (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to develop a website-based interactive media that meets the criteria of validity, practicality, and effectiveness in improving student learning outcomes of class V of elementary school on the learning material of facts and opinions The study employed the 4D development model (Define, Design, Develop, and Disseminate) However, this study was limited to the development stage, including limited-scale testing in the elementary school setting after the feasibility test. The feasibility of the website-based interactive media was evaluated by expert validators The validation results showed an average score of 96,25%, which is categorized as highly feasible for use by both teachers and students in elementary schools. To assess practicality, the researcher utilized a teacher observation sheet, which showed a total score of 47 out of a maximum of 48, with an average practicality percentage of 97,91%, indicating a highly practical category. Regarding effectiveness, implementation in class V of SDN 90 Sipatana, Gorontalo City, was measured using pretests and post-tests. The results showed an increase in the average score from 38,5% (pretest) to 86,5% (post-test), with a gain of 47,5%. The effectiveness level of the website-based interactive media reached 76,61%, indicating that it is effective in improving students' learning outcomes on the learning material of facts and opinions and is suitable for use in elementary school learning.